Ethnographies of Prostitution in Contemporary China - Zheng, T. author. aut Link
X, 244 p.
Keywords: This ethnographic study of prostitution in the metropolitan city of Dalian, China, explores the lives of rural migrant women working as karaoke bar hostesses, delving into the interplay of gender politics, nationalism, and power relationships that inhere in practices of birth control, disease control, and control of women's bodies.